2021
DOI: 10.1186/s12864-021-08196-8
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation regulates the expression of genes involved in worker reproduction in the ant Temnothorax rugatulus

Abstract: Background In insect societies, queens monopolize reproduction while workers perform tasks such as brood care or foraging. Queen loss leads to ovary development and lifespan extension in workers of many ant species. However, the underlying molecular mechanisms of this phenotypic plasticity remain unclear. Recent studies highlight the importance of epigenetics in regulating plastic traits in social insects. Thus, we investigated the role of histone acetylation in regulating worker reproduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 100 publications
0
22
2
Order By: Relevance
“…In the absence of a demand to switch task, C646 application did not result in behavioural alterations. This is the third study on Temnothorax ants, which revealed a role of HAT inhibition in modulating switches in workers, including circadian rhythms [33] and the induction of worker fertility [34]. Conversely, our results partly contradict a study on the ant Camponotus floridanus, in which HAT inhibition did not facilitate but reduce foraging activity in two morphologically distinct worker castes [29].…”
Section: Discussioncontrasting
confidence: 98%
“…In the absence of a demand to switch task, C646 application did not result in behavioural alterations. This is the third study on Temnothorax ants, which revealed a role of HAT inhibition in modulating switches in workers, including circadian rhythms [33] and the induction of worker fertility [34]. Conversely, our results partly contradict a study on the ant Camponotus floridanus, in which HAT inhibition did not facilitate but reduce foraging activity in two morphologically distinct worker castes [29].…”
Section: Discussioncontrasting
confidence: 98%
“…The relationship between DNA methylation and histone modifications in social insects remains unknown. However, recent work by Choppin et al (2021) shows a role for histone acetylation in the regulation of worker reproduction and gene expression in the ant Temnothorax rugatulus. Additionally, Dixon and Matz (2022) find gene-body methylation across a variety of invertebrates, including B. terrestris is not sufficient to fully explain changes in gene transcription, they also suggest a more complex regulatory mechanism may be in play involving other epigenetic modifications.…”
Section: B Terrestris Caste-and Sex-specific Methylomementioning
confidence: 99%
“…The relationship between DNA methylation and histone modifications in social insects remains unknown. However, recent work by Choppin et al . (2021) shows a role for histone acetylation in the regulation of worker reproduction and gene expression in the ant Temnothorax rugatulus .…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between DNA methylation and histone modifications in social insects remains unknown. However, recent work by Choppin et al (2021) shows a role for histone acetylation in the regulation of worker reproduction and gene expression in the ant Temnothorax rugatulus. Additionally, Dixon and Matz (2022) find gene-body methylation across a variety of invertebrates, including B. terrestris is not su cient to fully explain changes in gene transcription, they also suggest a more complex regulatory mechanism may be in play involving other epigenetic…”
Section: Discussionmentioning
confidence: 99%